U‐shaped association between body mass index and ejection fraction in intensive care unit patients with heart failure. (17th October 2022) - Liu, Hualong; Huang, Ying; Zhuo, Wen; Wan, Rong; Hong, Kui
Abstract: Aims: There are limited data about the relationship between body mass index (BMI) and left ventricular ejection fraction (EF) in patients with heart failure (HF). The study aims to assess the correlation between BMI and left ventricular EF under HF conditions. Methods and results: We derived the data from the Dryad Digital Repository for analysis, and the information of the original patients was obtained from the MIMIC‐III database by the data uploader. We performed smooth curve and two piecewise linear regression analyses to evaluate the association between BMI and EF in HF patients. A total of 962 participants were included in this study, with age of 73.7 ± 13.5 years, and 475 participants were male (49.4%). The results of the smooth curve supported a U‐shaped relationship between BMI and EF, and the inflection point was found to be a BMI of 23.3 kg/m 2 in these HF patients. After adjusting for potential confounders, we found that EF decreased with increasing BMI up to the inflection point (β = −0.7, 95% CI −1.3 to −0.1, P  = 0.028), whereas beyond the turning point, the relationship between EF and BMI showed a positive correlation (β = 0.2, 95% CI 0.1–0.3 P  < 0.001). Importantly, ischaemic heart disease (interaction P  = 0.0499) and hyperlipidaemia (interaction P  = 0.0162) affected the association between BMI and EF in the lower BMI group (BMI < 23.3 kg/m 2 ), although only diabetes mellitus (interaction P  = 0.0255) altered the association between BMI and EF in the higher BMI group (BMI ≥ 23.3 kg/m 2 ). Conclusions: In addition to higher BMI, we also found that lower BMI is related to higher EF in intensive care unit patients with HF, supporting a U‐shaped association between BMI and EF.